Breaking into acting for dummies - Garrison, Larry; Wang, Wallace (John Wiley and Sons, Inc., 2021)
"Breaking Into Acting For Dummies demystifies the behind-the-curtain side of showbiz to help you understand how it really works, who the decision-makers are, what they're looking for when they're picking talent, and how to get them on your side. Written by two friendly insiders, this guide will help you map out your plan of attack, showing you how to open doors--and keep them open--and use your time wisely. You'll understand how to flesh out your professional persona, craft your resume, and judge the angle of your headshots and webcam appearances. Once you've mastered these skills, it's time to go to market as your own publicity department, building your media and online presence until everyone who's anyone knows exactly who you are"-- Publisher's description.